Análise dos efeitos do derivado da chalcona, (E)-1-fenil-3-αnaftilprop-2-en-1-ona (NaF), em Phytomonas serpens - Santos, Tamiris Aparecida de Carvalho (2020)
The protozoan Phytomonas serpens belongs to the Trypanosomatidae family. This phytoparasite has a parasitism relationship with Solanum lycopersicum (L). (tomato), and has been used as a biological model for trypanosomatid bioassays. Chalcones are α, β insaturated cetons naturally occurring produced in plant secondary metabolism. In the chemical synthesis different modifications in chalcone can be made giving chalcone derivatives. These have the fundamental structure of chalcone and substitution of chemical groups to aromatic rings. These molecules presents several biological activities such as antibacterial, antifungal and antiprotozoal. The antimicrobial activity of molecules containing naphthalene is also well reported in the scientific literature and the derivative (E) -1-phenyl-3-α naphthylprop-2-en-1- one (NaF) presents substitution of the benzene ring B for a naphthalene ring. The objective of this work was to evaluate the antiprotozoal activity and the effect of the chalcone derivative (NaF) on the morphology and physiology of promastigote forms of P. serpens. The P. serpens isolate used was donated from the collection of trypanosomatids of the Oswaldo Cruz Foundation (Fiocruz). Promastigotes were maintained in Schneider medium supplemented with 10% fetal bovine serum and 1% streptomycin antibiotic and incubated in B.O.D. at 24 ± 1ºC. The NaF derivative was synthesized and characterized at the Chemistry Department of the Federal University of Sergipe. The antiprotozoal activity of the NaF was evaluated through bioassays of cell proliferation and permanent effect. The physiological effects evaluated were integrity of the plasma membrane, determination of ROS levels and depolarization of the mitochondrial membrane potential (∆ѱm) by spectrophotometry and flow cytometry, while the morphological ones by scanning and transmission electron microscopy. The results showed that treatment with the NaF after 24h promotes a reduction in the cell proliferation of P. serpens (IC50 21.52 µM), in addition to affecting important physiological processes, such as the oxidative balance and the potential of the mitochondrial membrane.The concentrations of 48 and 96 µM promoted a permanent effect, since the promastigotes exposed to these concentrations showed reduced growth. The concentration of 24 µM promotes swelling of the flagellar pocket and loss of flagellum in promastigote forms, in addition to the formation of concentric membrane structures within the parasite's mitochondria. However, the most recurrent phenotype observed was autophagy, including the appearance of autophagosomes, detected in different levels of cargo degradation, and endoplasmic reticulum profiles. Thus, it can be concluded that NaF showed antiprotozoal activity against P. serpens.The observed effects after NaF treatment were flagellum loss and autophagy phenotype.